Enriching m-banking perceived value to achieve reuse intention. Issue 6 (2nd September 2019) - Prodanova, Jana; Ciunova-Shuleska, Anita; Palamidovska-Sterjadovska, Nikolina
Abstract : Purpose: The purpose of this paper is to model the perceived value and customers' intention to continue using m-banking services, assuming the existence of multiple consumption values. Specifically, it is proposed that entertainment (hedonic value), ubiquity (utilitarian value) and novelty seeking (epistemic value) impact m-banking overall perceived value, which in turn influences customers' reuse intentions. Design/methodology/approach: A survey with 260 Macedonian current users of m-banking services was carried out, using questionnaires as a method of data collection. Five-point Likert scales adapted from the relevant literature to the context of m-banking services were used to measure the variables. PLS-SEM approach was employed to estimate the proposed model. Findings: The findings indicate that bank entities can increase customers' intention to reuse m-banking, by providing an enriched perceived value of m-banking services, precisely putting emphasis on perceived value drivers related to utilitarian value (ubiquity) and epistemic value (novelty seeking). Hedonic value (perceived entertainment) does not show a significant influence on the perception of m-banking value. Originality/value: This study provides a different perspective of the perceived value observation, by contemplating not only the well-established hedonic and utilitarian aspects of value, but also the epistemic component, considered as a vital element in contexts of mobile technologies adoption. Moreover, this is the first study to explore the m-banking perceived value in a developing country in the Balkans.